2021
DOI: 10.1080/21623945.2021.1938829
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-26a shuttled by extracellular vesicles secreted from adipose-derived mesenchymal stem cells reduce neuronal damage through KLF9-mediated regulation of TRAF2/KLF2 axis

Abstract: Yang (2021) microRNA-26a shuttled by extracellular vesicles secreted from adipose-derived mesenchymal stem cells reduce neuronal damage through KLF9-mediated regulation of TRAF2/KLF2 axis, Adipocyte, 10:1, 378-393,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…Also, Evs of MSCs transfected with miR-26a-5p and miR-221-3p mimic, respectively, attenuated ischemia/reperfusion injury and stroke (Ai et al, 2021 ; Cheng et al, 2021 ). A gain- and loss-of-function study showed that mir-26a is important for the neuroprotective effect of Evs from AT-MSCs in a model of ischemia/reperfusion (Hou et al, 2021 ). A recent study showed that viral transduction of MSCs may impact their miRNA cargo in Evs (Zubkova et al, 2021 ).…”
Section: Msc-derived Exosomes and Extracellular Vesicles (Evs)mentioning
confidence: 99%
“…Also, Evs of MSCs transfected with miR-26a-5p and miR-221-3p mimic, respectively, attenuated ischemia/reperfusion injury and stroke (Ai et al, 2021 ; Cheng et al, 2021 ). A gain- and loss-of-function study showed that mir-26a is important for the neuroprotective effect of Evs from AT-MSCs in a model of ischemia/reperfusion (Hou et al, 2021 ). A recent study showed that viral transduction of MSCs may impact their miRNA cargo in Evs (Zubkova et al, 2021 ).…”
Section: Msc-derived Exosomes and Extracellular Vesicles (Evs)mentioning
confidence: 99%
“…A great deal of miRNAs enveloped into MSC exosomes, such as miR-1-3p, miR-22-3p, miR-25, miR-26a, miR-26b-5p, miR-31, miR-126, miR-132, miR-138-5p, miR-146a-5p, miR-206, miR-223-3p, and miR-542-3p, were demonstrated to improve neuronal, astrocytic, oligodendrocytic, and microglial survival by downregulating target genes including KDM6B, p53, KLF9, CH25H, TRAF6, ACVR2B, LCN2, TLR4, RMRP, or CysLT2R. 38 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 Autophagy is also associated with the promotion of cell death via leading to cellular accumulation of toxic metabolites or cellular self-degradation. 88 Exosomal transfer of miRNAs from MSCs can reduce cell death by inhibiting excessive autophagy.…”
Section: Roles Of Exosomal Mirnas In Ischemic Strokementioning
confidence: 99%
“…More interaction effects and related molecular targets under ischemic stroke are summarized in Table 1 and Figure 3 . 38 , 63 , 65 , 67 , 69 , 70 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 89 , 90 , 91 , 92 , 93 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 …”
Section: Roles Of Exosomal Mirnas In Ischemic Strokementioning
confidence: 99%
See 1 more Smart Citation
“…Anesthesia: 9 studies [26,29,30,34,35,37,38,41,47] used pentobarbital; 3 studies [28,31,48] used chloral hydrate; 1 study [36] used chloral hydrate and xylazine; 5 studies [27,39,40,43,46] used isoflurane; 1 study [32] used ketamine; 1 study [44] used ether; 1 study [45] used isoflurane oxygen/nitrous oxide mixture; 1 study [49] used uratan; and 2 studies [33,42] [26,33,38,39,46,48,49]; by gradient centrifuge method (2 studies) [35,43]; or by adherence method (2 studies) [30,36]; or by centrifugation in combination with filtration methods (1 study) [40]; or by filtration methods (1 study) [28]. 11 studies [27,29,31,32,34,37,41,42,44,45,…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%